Alpha‐enolase 1 knockdown facilitates the proliferation and invasion of villous trophoblasts by upregulating COX‐2 - Huaiyun Tang; Linqing Pan; Lisha Tang; Jiayin Liu (Molecular Genetics & Genomic Medicine, 2023)
Abstract Background Enolase 1 (ENO1) is a metabolic enzyme which participates in pyruvate synthesis and ATP production in cells. Previously, differential expression of ENO1 was discovered in villous tissues between recurrent miscarriage and induced abortion. This study was designed to explore whether ENO1 influences the proliferation and invasion of villous trophoblasts and the related molecular mechanisms. Methods First, ENO1 expression in placental villus tissues collected from recurrent miscarriage (RM) patients and women for induced abortion as well as in trophoblast‐derived cell lines was detected by RT‐qPCR and western blotting. ENO1 localization and expression in villus tissues were further confirmed through immunohistochemistry staining. Then, the effects of ENO1 downregulation on trophoblast Bewo cell proliferation, migration, invasion, and epithelial‐mesenchymal transition (EMT) process were evaluated by CCK‐8 assay, transwell assay, and western blotting. As for the regulatory mechanism of ENO1, the expression of COX‐2, c‐Myc and cyclin D1 in Bewo cells after ENO1 knockdown was finally evaluated by RT‐qPCR and western blotting. Results ENO1 was mainly localized in the cytoplasm, with very small amounts in the nucleus of trophoblast cells. ENO1 expression in the villi tissues of RM patients was significantly increased, when compared with the villous tissues of healthy controls. Furthermore, Bewo cells, a trophoblast cell line with relatively higher expression of ENO1, was used to downregulate the ENO1 expression by ENO1‐siRNA transfection. ENO1 knockdown significantly facilitated Bewo cell growth, EMT process, migration, and invasion. ENO1 silencing markedly elevated COX‐2, c‐Myc, and cyclin D1 expression. Conclusion ENO1 may participate in the development of RM via suppressing the growth and invasion of villous trophoblasts via reducing the expression of COX‐2, c‐Myc, and cyclin D1.